Community Service through the Teaching and Learning Movement in Improving the Faith and Morals of Elementary School Students - Nurhasanah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
Basically the application of the Thematic Real Work Lecture (KKNT) system that has been implemented has an important influence on education, one of which is Islamic Religious Learning in Elementary Schools and other levels of Education. Learning Aqidah Akhlak is very important because later it will shape the attitude, behavior and identity of a child because high moral formation is the main goal in Islamic education. And talking about coaching issues is the same as talking about the goals of Islamic education. Coaching is an activity to maintain and perfect what already exists and is done repeatedly. Moral development must also be given to children from an early age and must be carried out by related parties such as parents, educational institutions, the government and other parties continuously so that they can have noble morals as exemplified by Rasulullah SAW and be able to stay away from bad morals. bad. Therefore, Islamic Religious Education teachers are required to provide role models and always pay attention to students both in terms of knowledge, attitude and behavior as well as worship skills to realize students who have noble character in accordance with the Islamic religion.